Epistemology and Quantitative Research - Yucra Quispe, Teófilo (2020)
This study presents a theoretical analysis between epistemology and quantitative research and the relationship of the indicated variables, from a theoretical perspective in higher education, for which the conceptual analysis of science has been used in both terms, determining that the Theoretical study of epistemological knowledge, is scientific knowledge in the field of epistemology, in the entire field of education that includes teachers and students; They have their appreciation, as part of the gnoseology or philosophy of science; however, the latter does not correspond. Quantitative research adds the paradigms of the facts, the structure of science, the verification of the hypotheses or doing the research to change a fact; moreover, it is considered as a statistical inference of the scientific method. The study includes two different and at the same time complementary terms in scientific knowledge, whose support is in the quantitative approach of the hypothetical - deductive method, which is included in the study of science; otherwise, both study variables are directed towards the scientific structure, scientific methodology and paradigms, pedagogy as educational didactics and epistemology in its descriptive, critical and science orientation task.